Mixed‐methods exploration of students' motivation in using augmented reality in neuroanatomy education with prosected specimens. Issue 5 (16th November 2021) - Bölek, Kerem A.; De Jong, Guido; Van der Zee, Catharina E. E. M.; van Cappellen van Walsum, Anne‐Marie; Henssen, Dylan J. H. A.
Abstract: The use of augmented reality (AR) in teaching and studying neuroanatomy has been well researched. Previous research showed that AR‐based learning of neuroanatomy has both alleviated cognitive load and was attractive to young learners. However, how the attractiveness of AR effects student motivation has not been discovered. Therefore, the motivational effects of AR were investigated in this research by the use of quantitative and qualitative methods. Motivation elicited by the GreyMapp‐AR, an AR application, was investigated in medical and biomedical sciences students ( n = 222; mean age: 19.7 ± 1.4 years) using the instructional measure of motivation survey (IMMS). Additional components (i.e., attention, relevance, confidence, and satisfaction) were also evaluated with motivation as measured by IMMS. Additionally, 19 students underwent audio‐recorded individual interviews which were transcribed for qualitative analysis. Males regarded the relevance of AR significantly higher than females ( P < 0.024). Appreciation of the GreyMapp‐AR program was found to be significantly higher in students studying biomedical sciences as compared to students studying medicine ( P < 0.011). Other components and scores did not show significant differences between student groups. Students expressed that AR was beneficial in increasing their motivation to study subcortical structures, and that AR could be helpful and motivating for preparing an anatomy examination. This study suggests that students are motivated to study neuroanatomy by the use of AR, although the components that make up their individual motivation can differ significantly between groups of students.